2017
DOI: 10.21608/bvmj.2017.31114
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical effect of resveratrol on Lipids profile and hepatic oxidative stress in experimentally induced obesity in female rats

Abstract: This study was designed to evaluate the effect of prolonged intake of resveratrol on lipid metabolism, liver enzymes and L-malondialdehyde(L-MDA) in obesity-induced in female rats by feeding high fat diet. Ninety female albino rats were divided into six equal groups of 15 rats each. Group Ι: rats fed normal control diet all over the periods of experiment (for 12 weeks). Group II: rats fed the control normal diet and administered resveratrol orally (0.1 mg/kg b.wt., orally) for 6 weeks. Group III: rats received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
(29 reference statements)
1
1
0
Order By: Relevance
“…Although the serum TG increased significantly at the 4 th week, it decreased significantly after 8 weeks, in HFD-fed animals revealing the effect of time of HFD feeding on serum TG level. These results were in agreement with Hussein et al [26] who recorded a significant increase in serum levels of TC, TG, very low density lipoprotein, and LDL, while the level of HDL was significantly decreased in obese female rats. In addition, Venkateshan et al [27] attributed that to the oxidative stress of HFD that highly correlated with a wide variety of inflammatory and metabolic disease states including obesity.…”
Section: Discussionsupporting
confidence: 93%
“…Although the serum TG increased significantly at the 4 th week, it decreased significantly after 8 weeks, in HFD-fed animals revealing the effect of time of HFD feeding on serum TG level. These results were in agreement with Hussein et al [26] who recorded a significant increase in serum levels of TC, TG, very low density lipoprotein, and LDL, while the level of HDL was significantly decreased in obese female rats. In addition, Venkateshan et al [27] attributed that to the oxidative stress of HFD that highly correlated with a wide variety of inflammatory and metabolic disease states including obesity.…”
Section: Discussionsupporting
confidence: 93%
“…Zhang et al [ 41 ] and Park et al [ 35 ] observed the same results in HFFD-fed rats. These disorders could be related to HFFD-mediated excessive delivery of fatty acids to the liver, resulting in the activation of oxidative stress and inflammatory pathways that promotes the escape of hepatic cellular enzymes [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%